Piezoelectric energy harvesting with an ultrasonic vibration source - Li, Tao (2019)
A piezoelectric energy harvester was developed in this paper. It is actuated by the vibration leakage from the nodal position of a high-power ultrasonic cutting transducer. The harvester was excited at a low displacement amplitude (0.73 µmpp). However, its operation frequency is quite high and reaches the ultrasonic range (24.4 kHz). Compared with another low frequency harvester (66 Hz), both theoretical and experimental results proved that the advantages of this high frequency harvester include (i) high current generation capability (up to 20 mApp compared to 1.3 mApp of the 66 Hz transducer) and (ii) low impedance matching resistance (500 Ω in contrast to 50 kΩ of the 66 Hz transducer). This energy harvester can be applied either in sensing, or vibration controlling, or simply energy harvesting in a high-power ultrasonic system.